If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(7n + -4) + 4n = 0 Reorder the terms: -3(-4 + 7n) + 4n = 0 (-4 * -3 + 7n * -3) + 4n = 0 (12 + -21n) + 4n = 0 Combine like terms: -21n + 4n = -17n 12 + -17n = 0 Solving 12 + -17n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -17n = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -17n = 0 + -12 -17n = 0 + -12 Combine like terms: 0 + -12 = -12 -17n = -12 Divide each side by '-17'. n = 0.7058823529 Simplifying n = 0.7058823529
| (3y+1)+25= | | 7.7(x-2)=-0.3x+40.6 | | -81=-9k | | 10x-5x=5 | | -8=a+3 | | -5(n-1)-4h= | | 1x^2-3x+2=0 | | -2(9p+5)= | | y=.75x+2 | | 6(d+1)= | | 6(2x+3)=-9 | | 3y-7+5y-9= | | -3(x-5)=3(x-1) | | -6(2+3)+52= | | 16y-22y= | | A=1/2*10(6+15) | | x^2=-5 | | x^2-25=2x | | 5(2+x)+2x=20-(2x+6) | | 3x-6x+2= | | x-7x+29=0 | | 10-8x=86-22x | | 0.8x+.18=.3(x+.2) | | 14x^5+6x^3= | | 10-8x=86-26x | | x^2+24x+106=0 | | 14x+7x-18=0 | | 3q+11+8q= | | 9x+3=8-6x | | -9(t+6)=0 | | f(7)=3(4-7) | | 5(4+c)=4(c-6) |